The Impact of Commuter Line (KRL) Travel Stress on Employee Performance in South Jakarta - Cynthia Chandra; Charli Sitinjak (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the effect of Commuter Line (KRL) commuting stress on employee performance in South Jakarta. The high mobility of workers from buffer zones to the Jakarta metropolitan area, coupled with overcrowding and operational uncertainty, is suspected to trigger commuting stress that may reduce work productivity. This research employed a quantitative approach with a cross-sectional correlational design. Data were collected using a questionnaire administered to 426 respondents selected through purposive sampling technique. The measuring instruments used were the Multimodal Commuting Stress Scale (MCSS) and the Individual Work Performance Questionnaire (IWPQ) version 1.0. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS 8.0 software. The findings indicate that Commuter Line (KRL) commuting stress has a significant and negative effect on employee performance in South Jakarta, with a path coefficient of -0.327 and a p-value < 0.001. The coefficient of determination (R²) of 0.107 indicates that commuting stress explains 10.7% of the variance in employee performance. This study confirms that the higher the level of commuting stress experienced by employees, the lower their performance at work. Commuting stress is not merely a routine activity but an external factor that contributes to fluctuations in employee performance. These findings provide theoretical contributions to industrial and organizational psychology, as well as practical recommendations for companies to consider flexible work policies to mitigate the negative impacts of commuting stress.